An Efficient Prediction Of Sentiment Analysis For Book Reviews Using Deep Learning - Mr. K.Karthik, S sandeep kumar, M.Jyothika, Y.Sethu Sruthi, S.Jyotheesh (International Journal of Advanced Science and Technology, 2020)
Sentiment has traditionally been considered a "deep" attribute of writing, often required the interpretation of figurative language to uncover the writer’s intention. Sentiment Analysis is one of the main challenges in natural language processing. Recently, deep learning applications have shown impressive results across different NLP tasks. In this project we did Sentiment Analysis on Amazon Book Reviews. We will be using Deep Neural Feed Forward Network for this Sentiment Analysis. Sentiment Analysis can be of three types: 1. Positive 2. Negative This analysis can be done using neural network. Using this method we calculated the positive and negative sentiment. Then we compared it with the actual result to and the accuracy.